Current and Emerging Pharmacotherapeutic Options for Smoking Cessation. (January 2013) - Carson, Kristin V.; Brinn, Malcolm P.; Robertson, Thomas A.; To-A-Nan, Rachada; Esterman, Adrian J.; Peters, Matthew; Smith, Brian J.
Tobacco smoking remains the single most preventable cause of morbidity and mortality in developed countries and poses a significant threat across developing countries where tobacco use prevalence is increasing. Nicotine dependence is a chronic disease often requiring multiple attempts to quit; repeated interventions with pharmacotherapeutic aids have become more popular as part of cessation therapies. First-line medications of known efficacy in the general population include varenicline tartrate, bupropion hydrochloride, nicotine replacement therapy products, or a combination thereof. However, less is known about the use of these products in marginalized groups such as the indigenous, those with mental illnesses, youth, and pregnant or breastfeeding women. Despite the efficacy and safety of these first line pharmacotherapies, many smokers continue to relapse and alternative pharmacotherapies and cessation options are required. Thus, the aim of this review is to summarize the existing and developing pharmacotherapeutic and other options for smoking cessation, to identify gaps in current clinical practice, and to provide recommendations for future evaluations and research.